2007
DOI: 10.1093/bfgp/elm006
|View full text |Cite
|
Sign up to set email alerts
|

Plant parasitic nematode proteins and the host parasite interaction

Abstract: This review focuses on the proteins and secretions of sedentary plant parasitic nematodes potentially important for plant-nematode interactions. These nematodes are well equipped for parasitism of plants. Having acquired the ability to manipulate fundamental aspects of plant biology, they are able to hijack host-cell development to make their feeding site. They feed exclusively from feeding sites as they complete their life cycle, satisfying their nutritional demands for development and reproduction. Biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…The FAR-1 protein binds to linolenic and linoleic acid, which are precursors of plant defence compounds in the jasmonic acid signaling pathway (Prior et al 2001;Curtis 2007). It was recently detected in the M. javanica cuticle surface and along the adjacent host root tissues and a continuous secretion of this protein into the intercellular space between the nematode body and the host cells was proposed (Iberkleid et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAR-1 protein binds to linolenic and linoleic acid, which are precursors of plant defence compounds in the jasmonic acid signaling pathway (Prior et al 2001;Curtis 2007). It was recently detected in the M. javanica cuticle surface and along the adjacent host root tissues and a continuous secretion of this protein into the intercellular space between the nematode body and the host cells was proposed (Iberkleid et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is present in the surface coat of potato cyst nematode species and binds fatty acids, including linoleic acids that are precursor of plant defence compounds (Prior et al 2001). These fatty acids are metabolized by lipoxygenase as part of the signalling pathway leading to the production of jasmonic acid and FAR-1 inhibited this biochemical process in vitro thus may have a role in the suppression of jasmonate synthesis and of the downstream signalling pathways, reducing host defences (Curtis 2007;Haegeman et al 2012). A study with M. javanica suggests that the MJ-FAR-1 protein has an important role in the infection process.…”
mentioning
confidence: 99%
“…de Almeida Engler et al (1999) reported that the enlarged nuclei and nucleoli in these expanding syncytia might be due to endocycles taking place within the feeding cells. The shape of esophageal glands also differs in the sedentary stages as compared to the motile 2 nd stage juvenile stage (Curtis, 2007) (Fig. 3A and B).…”
Section: Establishment Of Syncytia By Cyst Nematodes In Plant Rootsmentioning
confidence: 97%
“…Nematode genomes encode for proteins specific to the phylum Nematoda, and are critically important for understanding nematode biology [4][5][6]. Proteins specific to the phylum Nematoda are ideal targets for drugs with low toxicity to the host and the environment.…”
Section: Introductionmentioning
confidence: 99%